Bankruptcy Prediction Model: Altman (Z-Score), Springate (S-Score), Zmijewski (X-Score) And Grove (G-Score) Models in Companies Listed at The LQ 45 Stock Index - Ros Bunga Bondar; Mochamad Kohar Mudzakar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to assess the effectiveness of four prominent bankruptcy prediction models, namely Altman's Z-Score, Springate's S-Score, Zmijewski's X-Score, and Grove's G-Score, in forecasting financial distress among companies listed on the LQ 45 Stock Index. The research leverages financial data spanning a specified period to construct and evaluate the predictive capabilities of these models. By employing a sample of companies operating within the LQ 45 index, the study provides a comprehensive comparative analysis of the models' accuracy, sensitivity, and specificity in identifying firms at risk of bankruptcy. Additionally, this research investigates potential improvements or synergies that may arise from combining the predictive power of multiple models. The findings of this study contribute to the body of knowledge in corporate finance and offer valuable insights for stakeholders, investors, and policymakers involved in risk assessment and financial decision-making within the context of the Indonesian stock market.